SAKRALITAS RUMAH ADAT BANUA SUKU TORAJA MAMASA DALAM MEMBENTUK KONEKTIVITAS DAN KOLEKTIVITAS - Otniel Aurelius Nole; Tony Tampake (UNIVERSITAS SEBELAS MARET (UNS), 2024)
Traditional houses are attached to life because they are the space and place where indigenous people live. Generally, traditional houses in the Toraja tribe are known as tongkonan. Meanwhile, there is also another traditional house from the Toraja Mamasa tribe (West Toraja) as a sub-tribe of Toraja that has a special traditional house called banua. For the Toraja Mamasa people, the meaning of a traditional house is more than that. In fact, banua is not just a place to live, but a space that contains religious values within it. Indigenous people have beliefs about banua as a sacred traditional house. The purpose of this research is to argue the sacredness of the banua traditional house of the Toraja Mamasa tribe in shaping the connectivity and collectivity of indigenous peoples with local beliefs. This research used a qualitative approach with a realist ethnography research type. Data collection was conducted using interview techniques and documents, including the use of books and scientific articles. The results showed that the sacredness of the banua traditional house and the kitchen space (lombon) in particular became the basis for the formation of their connectivity and collectivity as indigenous peoples with local beliefs. The most sacred part is the kitchen. The sacredness of the banua socio-theologically functions to construct their communal identity and religiosity related to connectivity and collectivity.